2022
DOI: 10.1002/bse.2986
|View full text |Cite
|
Sign up to set email alerts
|

Friends or foes? A systematic literature review and meta‐analysis of the relationship between eco‐innovation and firm performance

Abstract: Eco‐innovation has gained currency as an effective means of addressing corporate environmental impacts. Yet the literature is inconclusive as to how different types of eco‐innovation influence different types of firm performance. This is problematic, as practitioners and policymakers will not embrace eco‐innovation unless there is clear evidence that through its implementation companies can achieve returns, not only on their environmental performance but also on their economic, social and operational performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 134 publications
(162 reference statements)
3
17
0
Order By: Relevance
“…, 2019; Larbi-Siaw et al. , 2022; Zheng and Iatridis, 2022). From the perspective of inhibition orientation, however, suggest that green activities would increase firms' operating costs and R&D investment in the short term, which in turn has a negative impact on economic performance (Huang and Li, 2017a; Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2019; Larbi-Siaw et al. , 2022; Zheng and Iatridis, 2022). From the perspective of inhibition orientation, however, suggest that green activities would increase firms' operating costs and R&D investment in the short term, which in turn has a negative impact on economic performance (Huang and Li, 2017a; Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is divided into two streams: promotion view or inhibition view. From the perspective of promotion orientation, green behavior could help to make contribution to unique competitive edge, thereby increasing earnings (Fernando et al, 2019;Larbi-Siaw et al, 2022;Zheng and Iatridis, 2022). From the perspective of inhibition orientation, however, suggest that green activities would increase firms' operating costs and R&D investment in the short term, which in turn has a negative impact on economic performance (Huang and Li, 2017a;Zhang et al, 2019).…”
Section: Contributions To Understanding Green Research Intensitymentioning
confidence: 99%
“…Therefore, it is essential to figure out banking performance through the adoption of GR-banking practices by banks. Literature divided organizational performance or firm performance into three categories, that is, environmental performance, operational performance and financial performance (Zhang & Yang, 2016; Zheng & Iatridis, 2022). Future studies related to GR-banking adoption or intention should consider banking performance.…”
Section: Findings and Recommendationsmentioning
confidence: 99%
“…Without ignoring relevant criticism questioning the value of such collaborations and highlighting coordination issues (Linder & Williander, 2017), studies have identified significant legal, environmental, competitive, and financial pressures favoring them (Veleva & Bodkin, 2018). Indeed, the economic and competitive challenges arising from the impacts of COVID‐19, along with climate change and increasing trends toward environmental regulation (Demirel et al, 2018; Zheng & Iatridis, 2022), leave little room for delays, promoting collaborations as meaningful and cost‐effective ways of ensuring successful CE implementation.…”
Section: Collaboration As Meaningful Means Of Ensuring Ce Implementationmentioning
confidence: 99%